Radiological assessment of ionizing radiation impact on the terrestrial non-human biota in Lithuania - Konstantinova, Marina; Prokopčiuk, Nina; Gudelis, Arūnas; Butkus, Donatas (Journal of Environmental Engineering and Landscape Management, 2015)
The quantitative assessment of radionuclides transfer to non-human biota using their activity concentration ratios is required for models of predictive doses of ionizing radiation. Based on long-term data regarding activity concentration of radionuclides in the top soil layer of the entire territory of Lithuania, and with the help of ERICA Assessment Tool – a software application that calculates dose rates to selected biota, we estimated the radiological impact on the terrestrial non-human biota with special emphasis on the protected areas located in the vicinity of Ignalina Nuclear Power Plant (INPP). Estimated total dose rates of artificial radionuclides – after-Chernobyl 137Cs and 90Sr as well as discharged by INPP – and natural radionuclides, such as 238U and 232Th, were found to be less than ERICA screening value of 10 μGy h–1. First published online: 25 Oct 2015